Vernacular buildings as tourism asset in Eastern Indonesia - Saraswati, Titien (Institut Teknologi Sepuluh Nopember, 2017)
Indonesia has many traditional or vernacular buildings that still exist right now. Those buildings have already functioned partly as tourism asset in their areas, but so many vernacular buildings remain untouchable. Whereas, in the context of tourism, there is cultural heritage which consists of three main components: (1) monuments, (2) architecture or buildings, (3) sites. When we look at vernacular buildings in Eastern Indonesia, the possibilities those buildings to be tourism asset are high. The question should be explored is: what kind of potencies that can be explored, and in turn can be â€œsoldâ€ as tourism asset for vernacular buildings in the villages in Eastern Indonesia? The objective of this paper is to investigate the potencies of cultural heritage from which have possibilities to be tourism asset in several vernacular spots in Eastern Indonesia: Bayan Village (Lombok), Nua One small village in Woloara Village, Sikka and Mbengu Villages (Flores), Boti and Maslete Villages (Timor). Methods to collect data by surveying on the spot to vernacular buildings in the above locations, also surveying related and competent persons. Method to analyse the data by examining the data with tourism theories. The finding is, the potencies of vernacular buildings that can be categorized as the asset of tourism in the above villages are so many, which are architectural styles and cultural festivals in the villages, and also include the approach such as rehabilitation, renovation, restoration, and conservation.